2005
DOI: 10.1007/s00244-005-0004-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate on the Tadpoles of Two Ranids (Rana catesbeiana andR. clamitans)

Abstract: Nitrate is a potential stressor of amphibian larvae. Previous research has shown variation in the effects of nitrate among species and even populations of amphibians. However, relatively few species and populations of amphibians have been examined for nitrate tolerance, especially from populations in the agricultural regions of the United States. Using a 15-day laboratory experiment, we investigated the effects of nitrate on the larvae of two species of anurans (Rana catesbeiana and R. clamitans) that are comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Within ephemeral ponds and wetlands, amphibian larvae often feed near the top of the food webs and may be particularly sensitive to changes in water chemistry (Freda & Dunson, 1986;Smith et al, 2006) and in the supply of food (Kupferberg, 1997;Pryor, 2003). Recently, Maerz et al (2010) demonstrated that the elemental composition (carbon-to-nitrogen ratio) of detrital litter in ephemeral ponds can directly affect the development and survival of larval amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…Within ephemeral ponds and wetlands, amphibian larvae often feed near the top of the food webs and may be particularly sensitive to changes in water chemistry (Freda & Dunson, 1986;Smith et al, 2006) and in the supply of food (Kupferberg, 1997;Pryor, 2003). Recently, Maerz et al (2010) demonstrated that the elemental composition (carbon-to-nitrogen ratio) of detrital litter in ephemeral ponds can directly affect the development and survival of larval amphibians.…”
Section: Introductionmentioning
confidence: 99%
“…The global decline of amphibians has spurred interest in understanding how various environmental contaminants, including pesticides and fertilizers, impact the growth and development of amphibians [1][2][3][4][5][6][7][8]. This is because contamination of surface waters in agricultural landscapes by nitrogenous-or phosphorus-based fertilizers is widespread [9][10][11] and likely to continue or even increase [12], and pesticides frequently run off into local surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of pesticide exposure can vary among species of amphibians, and a variety of direct and indirect effects may be observed [3,[13][14][15]. Nitrate, a common fertilizer, has been shown to affect feeding, locomotion, development, and survival of amphibians [4][5][6][16][17][18]. However, the effects of nitrate can vary among species, with some species appearing to be relatively tolerant of nitrate exposure [4,19].…”
Section: Introductionmentioning
confidence: 99%
“…Although ammonia is the predominate form of nitrogenous waste produced by fish, fish may actually be more susceptible to ammonia toxicity than invertebrates [98]. Ammonia also causes decreased fitness in amphibians [99,100,101]. In general, direct amphibian mortality occurs at concentrations that would be considered high even in an agricultural setting [100].…”
Section: Impacts Of Agricultural Expansionmentioning
confidence: 99%
“…Not surprisingly, however, toxicity varies among species. Green frog tadpoles ( Rana clamitans ) exposed concentrations of nitrate 5 mg/L–20 mg/L demonstrated a significant increase in mortality compared to those reared at lower concentrations [101]. Even aquatic plants, such as rice ( Oryza sativa ) which would be expected to thrive under a high-nitrogen regime, can display toxicity under high concentrations of ionic ammonium [102].…”
Section: Impacts Of Agricultural Expansionmentioning
confidence: 99%